If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 15 = 8 Reorder the terms: 15 + -7x = 8 Solving 15 + -7x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -7x = 8 + -15 Combine like terms: 15 + -15 = 0 0 + -7x = 8 + -15 -7x = 8 + -15 Combine like terms: 8 + -15 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| -6n(5+8n)=-366 | | X^2+2x*1=0 | | 13=8+5t | | -7(t)=10t-19 | | 15+3x-15= | | 3log(4x+9)=10 | | 5x=20(x-2) | | 5x-10+10x=-6 | | 6x+4=x-4 | | 5x^2+6+1= | | 300=4.9t^2 | | 8x+24-2x=0 | | 180=x+x*3 | | 2x+12-8x=17-19x+13x-5 | | (x-9)*x=36 | | X-9*x=36 | | 5y+90=6x | | 5x+4y-3(5x-2y)= | | gs+5=16 | | 6[n-4]=3n | | 6+1x=3 | | 7+6(-6a+7)=-167 | | (2x+7)(5x+2)(x-4)=180 | | 8-2x=-1 | | 7d^4=35d^3 | | 6(7a+4)-4a=100 | | -3x^6= | | 32=35x | | 2x+6-6x+13=26x-45 | | 2.5x^2-2=3 | | x-.06x=24.44 | | 50+0.10m=45+0.30m |